Long-term relative survival from melanoma in Germany 1997-2013 - Brunssen, Alicia; Jansen, Lina; Brenner, Hermann (Melanoma research, 2020)
Up-to-date melanoma relative survival (RS) estimates and trend analysis facilitate close monitoring of melanoma patients’ prognosis. This study aimed to provide recent 5-year and 10-year RS from melanoma, stratified by prognostic factors, and identify latest survival trends. Data from 12 German cancer registries were analysed. We included patients with primary cutaneous malignant melanoma (ICD-10: C43.X) diagnosed in 1997-2013 who were at least 15 years old. Five-year and 10-year RS were estimated by period analysis. For 10-year RS analyses, we excluded patients who were 75 years of age or older. Analyses were stratified by sex, age, histology, tumour stage, and body site. We included 82 901 patients, of whom 51% were women. The median age at diagnosis was 62 years. Five-year and 10-year RS in 2007-2013 were 92.4 and 90.8%, respectively. RS was higher in women. The prognosis worsened with older age and higher stage. In superficial spreading melanoma and lentigo maligna melanoma, RS was high; it was lower in nodular, acral lentiginous and ‘other’ melanoma. RS was the highest for melanoma on the arms; RS for melanoma on unknown or overlapping sites of the skin was the lowest. Five-year and 10-year RS increased significantly from 2005-2007 and 2008-2010 to 2011-2013, by 3.5 and 3.3 percentage points, respectively. For melanoma of ‘other’ histology, 5-year and 10-year RS increased significantly. Ten-year RS also increased significantly in men with superficial spreading melanoma and T4 melanoma, and in women with T3 melanoma. Melanoma RS improved, especially in certain subgroups. The reasons for improvements need to be investigated further.